Ultrasound vs Nerve Conduction Studies: A Comparative Analysis in Carpal Tunnel Syndrome Diagnosis - Hasnawi Haddani; Henry Sugiharto; Afriani; Theresia Christin; Legiran; Ferawaty (HM Publisher, 2024)
Background: Carpal tunnel syndrome (CTS) is a prevalent entrapment neuropathy. While nerve conduction studies (NCS) remain the gold standard for diagnosis, ultrasound (USG) offers a non-invasive alternative. This study aimed to compare the diagnostic accuracy of USG and NCS in CTS at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia. Methods: A cross-sectional study was conducted on patients presenting with CTS symptoms. Demographic and clinical data were collected. NCS and USG assessments were performed, blinded to each other's results. USG measurements included the cross-sectional area at the carpal tunnel inlet (CSAc), proximal to the carpal tunnel (CSAp), and the difference between them (∆CSA). Diagnostic accuracy was calculated, and agreement was assessed using Cohen's kappa. Results: A total of 86 wrists from 49 patients were included. The mean age was 52 ± 11 years, with a female predominance (86%). The majority had mild CTS based on NCS (55.8%). USG measurements showed mean CSAc of 13.1 ± 3.5 mm², CSAp of 10.6 ± 3.0 mm², and ∆CSA of 2.5 ± 0.9 mm². ∆CSA had the highest sensitivity (92.2%), specificity (88.9%), and accuracy (91.9%), with substantial agreement with NCS (Kappa = 0.65). Conclusion: USG, particularly using ∆CSA, demonstrates high diagnostic accuracy in CTS, comparable to NCS. It can serve as a valuable tool, especially in settings with limited NCS availability.